Smokeless - Weng, Yayu (2019)
Tobacco Smoking is prevalent across different time periods, geographical positions and demographic groups. In Singapore, the government has been working hard to reduce the number of smokers since 1992. Smoking cessation has always been a challenge for many smokers due to their nicotine addiction and perceived benefits. However, by managing the cigarette intake of smoker, gradual changes to their smoking habit can be introduced. Overtime, their smoking habits can be curbed. Smokeless will be a system that provides the smoker with motivation and restraint that they require through the tough journey of smoking cessation.